(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2020)
Through the construction of an analysis tool that collects different categories and characterizations of timbre and timbre modulations, this work addresses the sound components, the timbral resultant, movements and transformations in time of the work “Music for eight playing things” of the Brazilian composer Jorge Antunes, describing the different types of timbral behaviors and interpreting the place and function of the textures, seeking a systematicity within the work. As a reflection, we could observe that by including the word ‘persons’ in the title of the piece, the composer possibly invites non-musicians to interpret it. In addition to this, the composer makes use of an intuitive proportional notation. Moreover, this work reflects important elements of timbral and electroacoustic thought.